Estimating bearing response in symmetric and asymmetric-plan isolated buildings with rocking and torsion. - Ryan, Keri L. (Earthquake engineering & structural dynamics.)
A comprehensive approach is developed to estimate relevant design quantities?lateral deformations and axial forces?in isolation systems composed of lead?rubber bearings. The approach, applicable to symmetric and asymmetric-plan systems, includes the effects of bidirectional excitation, rocking, and torsion; and is the culmination of previous work on this topic. The approach is based on nonlinear response history analysis of an isolated block using an advanced bearing model that incorporates the interaction between axial force and lateral response of the bearing, known as axial-load effects. The rocking response of the system and peak axial forces are shown to depend on the isolation period, the normalized strength?or yield strength normalized by peak ground velocity, the ratios of rocking frequency about each horizontal axis to vertical frequency, and the normalized stiffness eccentricity. In an attempt to develop results widely applicable to asymmetric-plan systems, eccentricity is introduced by varying the stiffnesses and strengths of individual bearings in an idealized, rectangular plan. This idealized system approach is shown to have limited success; when applied to actual asymmetric-plan systems the design equations to estimate response are accurate for lateral deformations but err by up to 25% for axial forces.